1, 2, 3, 4-Butanetetracarboxylic Acid Cross-Linked Softwood Kraft Pulp Fibers for Use in Fluff Pulp Applications. Issue 3 (September 2014) - Lund, Kristoffer; Brelid, Harald
Cross-linked fluff pulp fibers for use in, for example, acquisition layers in absorption products can be found in the patent literature. Cross-linking improves properties such as the wet resilience of fluff pulp fiber networks. Among the more commonly seen cross-linkers are polycarboxylic acids, such as 1, 2, 3, 4-butanetetracarboxylic acid (BTCA). These acids form ester bonds with the hydroxyl groups in the fiber wall. In this study, softwood kraft pulp fibers were cross-linked with BTCA. The swelling behavior of the fibers and properties related to acquisition in absorption products were studied. It was found that the water retention value (WRV) decreased as a consequence of the introduced cross-linker. After deprotonization of a large part of the introduced carboxylic acids, the WRV increased, but the cross-linker was still able to limit significant swelling of the fiber wall. The wet bulk under load of fiber networks, composed of cross-linked fibers, generally increased with a decrease in WRV. Furthermore, it was found that the property development obtained after a cross-linking reaction with BTCA may be predicted by introducing a relative reaction intensity, RIrel, that takes into account both time and temperature in the curing step. This shows that the time and temperature in the curing step are interchangeable.